Updating the Content of Higher Education in the Context of Modern Sociocultural Trends - E. E. Shishlova (Высшее образование в России)
In the article, on the basis of the culturological concept of the content of education as an adapted social experience, as well as the practice of its implementation in vocational training as purposeful and declared, the essence of its explicit, hidden and implicit components is differentiated for the first time. The leading role of the hidden content of education in the transmission of sociocultural values is revealed, which ensures the formation of the value-worldview characteristics of the personality of a competent graduate, capable of effective professional activity in the conditions of sociocultural transformations of the postindustrial era. The dynamic structure of the hidden education content is revealed, which includes communicative and subject components and which made it possible to determine the directions of its update by the sociocultural aspect. The update of the education content in the context of the growing role of the cultural factor in social development is realized through the sociocultural reflection of the transmitted social experience, for the development of which the diagnostic-forming methodology “My sociocultural values” has been developed. As a result of the update of the hidden education content by the sociocultural aspect, it is transformed into an implicit (updated hidden), which, while not being declared, but being adapted and purposeful in reflecting and translating sociocultural experience, improves the training of specialists in various directions and profiles, implements the leading principle of higher education.